An evaluation of the amount of grain and roughage to food at different stages of the feeding period - Perry, H.B.; Boren, D.W. (Kansas Agricultural Experiment Station, 2011)
The 30 steers used were good to choice Herefords purchased as claves near Sterling, Kansas, and allotted to 3 lots of 10 steers each. Unlimited roughage was fed where grain was restricted. A ratio of 1 part roughage to 3 parts grain was fed on full feed. Protein supplement was fed at 2lb. per head daily to all lots.
Keywords: Beef; Protein; Roughage; Sorghum grain; Gain